Chinese patients with adrenoleukodystrophy and Zellweger spectrum disorder presenting with hereditary spastic paraplegia. (August 2019) - Chen, Yi-Jun; Wang, Meng-Wen; Dong, En-Lin; Lin, Xiao-Hong; Wang, Ning; Zhang, Zai-Qiang; Lin, Xiang; Chen, Wan-Jin
Abstract: Introduction: X-linked adrenoleukodystrophy (ALD) and Zellweger spectrum disorder (ZSD) are peroxisomal diseases characterized by accumulation of very long chain fatty acids (VLCFA) in plasma and tissues. Considering the wide variability of manifestation, patients of ALD and atypical ZSD are easily misdiagnosed as hereditary spastic paraplegia (HSP) on their clinical grounds. Here, we aimed to determine the frequency of peroxisome diseases and compare their phenotypic spectra with HSP. Methods: We first applied targeted sequencing in 120 pedigrees with spastic paraplegia, and subsequently confirmed 74 HSP families. We then performed whole exome sequencing for the probands of the 46 remaining pedigrees lacking known HSP-causal genes. Detailed clinical, radiological features, and VLCFA analyses are presented. Results: Seven ALD pedigrees with ABCD1 mutations and one ZSD family harboring bi-allelic mutations of PEX16 were identified. Clinically, in addition to spastic paraplegia, four ALD probands presented adrenocortical insufficiency, and the ZSD proband and her affected sister both developed thyroid problems. VLCFA analysis showed that ratios of C24/C22 and C26/C22 were specifically increased in ALD probands. Moreover, three ALD probands and the ZSD proband had abnormalities in brain or spinal imaging. Conclusions: Our study reports the first ZSD case in China that manifested spastic paraplegia, and emphasized the finding that peroxisomal diseases comprise a significant proportion (8/120) of spastic paraplegia entities. These findings extend our current understanding of the ALD and ZSD diseases. Highlights: Report four novel mutations in ABCD1 and PEX16 genes. Expand the phenotypes of patients with PEX16 mutations. Perform a comprehensive analysis to distinguish peroxisomal diseases from complicated HSP. Present the high incidence (8/120) of peroxisomal diseases in spastic paraplegia spectrum.